Multifaith Room for Pediatric Cancer Center of Barcelona—An Intrahospital Public Space in the City - Arboix-Alió, Alba (Religions, 2024)
The internationalization of specialized healthcare emphasizes multiculturalism, requiring adaptable hospital spaces. Sant Joan de Déu (SJD), a leading pediatric hospital managed by a Christian order, has created a multifaith room for prayer and meditation in the main lobby of the Pediatric Cancer Center Barcelona (PCCB). This manuscript presents an unpublished case study, showing the research conducted for the design of the multireligious room and the process of its construction. The methodology includes a bibliographic review, architectural analysis of three meditation spaces, and in-depth interviews with stakeholders. This project highlights SJD’s commitment to blending care and design, emphasizing the humanization of hospital spaces. The triad of religion, public space, and society makes more sense here than ever before.